Normal and abnormal breath sounds Heart and breath sounds - Medcom Trainex (Cypress, CA : Medcom Trainex, 1986)
Auscultation of breath sounds is a valuable technique for assessing the patient's pulmonary function and status.This program introduces the physiology and acoustic characteristics of normal breath sounds and identifies patho-physiologic components of abnormal and adventitious sounds.
Keywords: Respiration